A new species and new records of the genus Bolboceras Kirby, 1819 (Coleoptera: Geotrupidae: Bolboceratinae) from India - Kalawate, Aparna; Hillert, Oliver (Zootaxa, 2018)
The genus Bolboceras Kirby, 1819 (Coleoptera: Geotrupidae: Bolboceratinae: Bolboceratini) currently contains more than 20 species, which are distributed from Lebanon in the Palaearctic region and eastern Africa through Pakistan, India, and Myanmar in the Oriental Region (Král et al. 2006; Krikken 2011, 2013a, 2013b; Nikolajev et al. 2016; Gupta & Chandra 2016a, 2016b). Krikken (2013a, 2013b) and Gupta & Chandra (2016a, 2016b) conducted recent taxonomic studies on the Oriental members of the genus. Species groups can be identified using the following characters: the shape of laterally rounded eye canthus with anterior protrusion, presence of interocular ridge, quadrituberculate pronotum, medially marginate pronotal base, elytral stria 1 not reaching the base, mesocoxae separated by a simple (non-hooked) meso-metaventral process, lack of grooves on outer side of last lamella of antennal club and limited sexual dimorphism (Krikken 2013a).